American nights entertainment - Overton, Grant M. (Grant Martin), 1887-1930 (D. Appleton & Co.: George H. Doran Company: Doubleday, Page & Co.: Charles Scribner's Sons, 1923)
This book presents advice for readers of the early 20th century by providing biographical sketches and insights into the works of popular authors John Galsworthy, Joseph Conrad, Arthur Train, V. Sackville-West, Harold Bell Wright, Ralph Connor, Booth Tarkington, Donald Ogden Stewart, Zona Gale, Gene Stratton-Porter, Joseph C. Lincoln, Edith Wharton, Christopher Morley, and Lothrop Stoddard. Reading suggestions by genre are also offered.